A questionnaire-based investigation of the skills and roles of Computer Music Designers. (September 2016) - Zattra, Laura; Donin, Nicolas
Throughout the history of electroacoustic music, creative collaboration has been a constant feature due to the complexity of the technology. All laboratories and electronic music studios involved the presence of different individuals with diverse, intertwined competencies. In particular, the embedding of technological tools into the process of musical creation prompted the rise of a new "agent" called the Computer Music Designer (CMD), who can work in writing, creating new instruments, recording and/or performance. Audiences as well as the academia have long been unaware of this emerging profession and its crucial role in the creative process of electroacoustic, electronic and computer music. This study sheds light on the socio-professional profile and expertise of the CMD in order to better understand how computer music design contributes to shaping electronic music as we know it. We present the methodology and outcomes of a questionnaire submitted to several CMDs. The purpose was to investigate this emerging community by means of an instrument permitting anonymity. Findings help to understand how the CMDs perceive their profession; trace common paths and habits among CMDs; and study this community from the point of view of their age, training, tasks, legal status, recognition, skills, professional identity and involvement in technological migration. The questionnaire instrument is appended.